The Milkfish Broodstock-Hatchery Research and Development Program and Industry: A Policy Study - Danilo C. Israel (Philippine Institute for Development Studies (PIDS), 2000)
This paper looks into the national R&D program for the production of hatchery-bred milkfish fry and the fledgling industry it has spawned with the end purpose of recommending courses of actions that the national government can pursue for their furtherance. The study concludes that hatchery-bred fry is necessary for milkfish culture to attain sustainable growth and international competitiveness in the coming years. Therefore, the government should continue to strongly support the R&D program and industry by exerting concrete measures to address the various technical, market, institutional and other problems which hinder them from fully becoming a vehicle of growth in the fisheries sector.
Keywords: 330; fisheries sector; Aquakultur; Forschung; Philippinen